The Scope of HbA1c Variability and Risk of Vascular Complications Among Patients with Type 2 Diabetes: A Systematic Review and Meta-Analysis of Prospective Studies - Guo, Kai; Zhao, Qian; Wang, Meng; Lu, Yuchun; Wo, Meihong; Zhou, Xiaoyan; Ying, Changjiang (Hormone and Metabolic Research, 2022)
Glycated hemoglobin (HbA1c) variability is emerging as an indicator of long-term glycemic control, which may play a significant role during vascular complications. We conducted a systematic review and meta-analysis to assess the association between the scope of HbA1c variability and vascular complications in patients with type 2 diabetes mellitus. PubMed and Embase were searched for studies that evaluated the association of HbA1c variability with vascular complications in patients with type 2 diabetes. Two reviewers independently completed data extraction. Random-effects meta-analysis was conducted with stratification according to the type of vascular complications. Nine studies were eligible for inclusion in our systematic review and meta-analysis. Six studies evaluated the impact of the standard deviation of HbA1c (HbA1c-SD) on cardiovascular events and showed an association of HbA1c-SD with cardiovascular events (HR: 1.25, 95% CI 1.18–1.32, 5 studies). Six studies evaluated renal disease associated with HbA1c-SD and showed that HbA1c-SD was correlated with an increased risk of renal disease (HR: 1.19, 95% CI 1.13–1.24). Two studies evaluated HbA1c-SD and the risk of retinopathy and showed that no significant association was found between retinopathy and HbA1c-SD (HR 1.08, 95% CI 0.92–125). For HbA1c-SD ranging from 0.6 to 0.8%, HbA1c-SD was associated with an increased risk of cardiovascular events (HR: 1.25, 95% CI 1.15–1.35) and renal disease (HR: 1.16, 95% CI 1.11–1.22). For individuals with index HbA1c variability greater than or equal to 0.6%, HbA1c variability was significantly associated with vascular complications in patients with type 2 diabetes mellitus.
Keywords: HbA1c variability; type 2 diabetes; vascular complications; meta-analysis